2003
DOI: 10.2134/agronj2003.1525
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Nitrogen Fertilization in Wheat under Conventional and No‐Tillage System

Abstract: tion rates and greater immobilization generated by surface residues (Rice and Smith, 1984).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
32
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 21 publications
6
32
1
Order By: Relevance
“…This excess water might have decreased the difference in grain yield between fertilization times. The lack of difference between fertilization times observed at Tandil grain yield for fertilization at tillering compared with fertilization at sowing was also reported by Videla et al (1996Videla et al ( , 2004 and Melaj et al (2003) at Balcarce and by Lo´pez-Bellido et al (2005) for Mediterranean conditions, in which 50-60% of total annual rainfall was recorded during fall and winter.…”
Section: Grain Yieldsupporting
confidence: 76%
See 2 more Smart Citations
“…This excess water might have decreased the difference in grain yield between fertilization times. The lack of difference between fertilization times observed at Tandil grain yield for fertilization at tillering compared with fertilization at sowing was also reported by Videla et al (1996Videla et al ( , 2004 and Melaj et al (2003) at Balcarce and by Lo´pez-Bellido et al (2005) for Mediterranean conditions, in which 50-60% of total annual rainfall was recorded during fall and winter.…”
Section: Grain Yieldsupporting
confidence: 76%
“…Average RE across site-years was 32 and 41% of applied N for fertilization at sowing and tillering, respectively. Melaj et al (2003) and Lo´pez-Bellido et al (2005), working with 15 N under rainfed conditions, reported RE values that ranged from 12 to 24% and from 16 to 52% for fertilization at sowing and tillering, respectively.…”
Section: Grain Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Kelley (2001) found no effect of N on kernel numbers per spike. Kernel weight has been reported to decrease with increased N rates (Batey and Reynish, 1976;Melaj et al, 2003). As expected, most of yield gains from a fungicide application after flag leaf emergence have been associated with increased kernel weight (Ruske et al, 2003b;Olesen et al, 2000;Kelley, 2001), but the current study indicates that fungicides have the greatest impact on kernel weight when N rates are increased.…”
Section: Nitrogen Rate × Fungicide Interaction Effect On Winter Wheatsupporting
confidence: 58%
“…Lower kernel weight with increased N has been reported in several studies (Batey and Reynish, 1976;Melaj et al, 2003), while others report responses to vary depending on the year (e.g., Olesen et al, 2000). It was shown in this study that head density and kernel number tended to increase with N rate; limited resources within the plant were likely divided among more kernels, which resulted in lower kernel weights as N rates were increased (Campbell et al, 1977).…”
Section: Nitrogen Rate × Fungicide Interaction Effect On Winter Wheatsupporting
confidence: 58%